Global engagement in R&D: A portrait of biopharmaceutical patenting firms - Laura Abramovsky (Institute for Fiscal Studies (IFS), 2015)
This paper provides a novel portrait of firms engaging in the international use of inventors. I focus on drug discovery activity of pharmaceutical and biotechnological firms head-quartered in Europe, over the period 1996-2005. An important part of the most high-valued added R&D activities are conducted by inventors, who are engaged in the creation of new technologies. I use a novel and particularly rich dataset that provides a comparable picture across host locations and over time of research activity of EU firms. The main results are that firm-level heterogeneity is a key feature in the internationalisation of inventors and this is similar to patterns from data analysing good and service traders and MNEs. Furthermore, host country distance characteristics are associated with the number of inventors in a similar fashion to patterns found in gravity models explaining good and service trade.
Keywords: F14; F19; F23; O31; 330; International trade; multinational firms; inventors; R&D